AB0689 Interstitial lung disease in severe connective tissue diseases (CTD). (23rd January 2014) - Danieli, M.G.; Moretti, R.; Gambini, S.; Paolini, L.; Gabrielli, A.
Abstract : Background: We here report the incidence, the clinical features and treatment response of interstitial lung disease (ILD) associated to idiopathic inflammatory myopathies (IIM), Sjogren's Syndrome (SS) and systemic lupus erythematosus (SLE). Methods: We reviewed the clinical notes of 224 consecutive patients followed by our department from 1990 to 2011. IIM was present in 77 patients, SS in 100 subjects and SLE was documented in 87 cases. Demographic, clinical and serological data were collected through a standardised protocol. ILD was defined by specific spirometric and tomographic patterns. Results: ILD was documented in 20 (26%) patients with IIM, in 15 (15%) with SS and in 13 (15%) with SLE. All patients were treated with steroid, alone or associated with an immunosuppressant. All of them had a restrictive pattern at the pulmonary function testing with a reduced diffusing capacity for carbon monoxide. In patients with SS- and LES- associated ILD the response to the treatment was satisfactory, whereas in patients with myositis, ILD-related deaths occurred in 25% of the cases. This percentage was higher when compared to the percentage of the disease-related death (17%). Conclusions: Despite major progress in the treatment, ILD in the course of CTDs remain a severe complication, significantly affecting subjects' survival and quality of life. The relatively high frequency of asymptomatic subjects, with subclinical ILD documented by the presence of a restrictive spyrometric pattern and typical radiological features, suggests the importance of early diagnosis. Disclosure of Interest: None Declared